2021
DOI: 10.1371/journal.pbio.3001130
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic effects on carbon cycling processes in soils

Abstract: Microplastics (MPs), plastic particles <5 mm, are found in environments, including terrestrial ecosystems, planetwide. Most research so far has focused on ecotoxicology, examining effects on performance of soil biota in controlled settings. As research pivots to a more ecosystem and global change perspective, questions about soil-borne biogeochemical cycles become important. MPs can affect the carbon cycle in numerous ways, for example, by being carbon themselves and by influencing soil microbial processes,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
128
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(133 citation statements)
references
References 53 publications
3
128
0
2
Order By: Relevance
“…Changes in soil structures (bulk density, water stable aggregates, water‐holding capacity, pore volume) associated with the presence of microplastics can directly affect soil microbial communities, which are the main drivers of nitrogen cycling (Rong et al, 2021), carbon processing (Rillig et al, 2021) and other biogeochemical processes essential for human survival (Bender et al, 2016). Multiple studies have shown that microplastics can affect soil microbial activity and may have important implications for nutrient cycling (de Souza Machado et al, 2019; de Souza Machado, Lau, et al, 2018; Liu et al, 2017; Rong et al, 2021).…”
Section: Microplastic Effects On Soil Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in soil structures (bulk density, water stable aggregates, water‐holding capacity, pore volume) associated with the presence of microplastics can directly affect soil microbial communities, which are the main drivers of nitrogen cycling (Rong et al, 2021), carbon processing (Rillig et al, 2021) and other biogeochemical processes essential for human survival (Bender et al, 2016). Multiple studies have shown that microplastics can affect soil microbial activity and may have important implications for nutrient cycling (de Souza Machado et al, 2019; de Souza Machado, Lau, et al, 2018; Liu et al, 2017; Rong et al, 2021).…”
Section: Microplastic Effects On Soil Structure and Functionmentioning
confidence: 99%
“…There is conflicting evidence about the role of microplastics in the terrestrial carbon cycle (Gao et al, 2021; Ren et al, 2020; Rillig et al, 2021). Carbon is the main element in microplastics and unlike more labile carbon sources that originate from natural processes (photosynthesis or biomass production), this recalcitrant carbon pool is better able to resist degradation, thus affecting soil carbon storage (Rillig & Lehmann, 2020).…”
Section: Microplastic Effects On Soil Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pinpointing environmentally relevant contamination levels remains difficult at this time, as publicly available large-scale terrestrial monitoring data and standardized quantification campaigns are limited or lacking altogether. In addition, a focus should be on potentially future, higher levels of this contaminant, at least within a global change biology framework (Rillig et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…But the ubiquitous particles appear to be interfering with the very fabric of the soil environment itself, by influencing soil bulk density and the stability of the building blocks of soil structure, argue Matthias Rillig and colleagues in their Essay. Microplastics can affect the carbon cycle in numerous ways, for example, by being carbon themselves and by influencing soil microbial processes, plant growth, or litter decomposition, the authors argue in "Microplastic effects on carbon cycling processes in soils" [7]. They call for "a major concerted effort" to understand the pervasive effects of microplastics on the function of soils and terrestrial ecosystems, a monumental feat given the immense diversity of the particles' chemistry, aging, size, and shape.…”
mentioning
confidence: 99%